BONS CAMINHOS PARA CHEGAR AO TERMO: PROCESSO CENTRAL NO TRABALHO TERMINOLÓGICO VOLTADO PARA A TRADUÇÃO ENTRE A PRÁTICA E O ENSINO - Mayer, Felix (Organon, 2011)
This text discusses some aspects concerning terminological theory and practice. Itstarts from the questioning on how to find equivalent terms in the working languages. Thephases and stages of the monolingual bilingual and/or multilingual terminological work arepresented as well as some ways to help the collection and validation of terms in the targetlanguage after the terminological analysis in the source language such as the use ofdictionaries and terminological termbanks, the intuitive term creation, horizontal and verticalapproach and specialist consultation.